Eating identities : reading food in Asian American literature - Xu, Wenying (UPCC book collections on Project MUSE., 2008)
'Eating Identities' is the first book to link food to a wide range of Asian American concerns such as race and sexuality. Xu provides lucid and informed interpretations of seven Asian American writers (John Okada, Joy Kogawa, Frank Chin, Li-Young Lee, David Wong Louie, Mei Ng, and Monique Truong), revealing how cooking, eating, and food fashion Asian American identities in terms of race/ethnicity, gender, class, diaspora, and sexuality. Most literary critics perceive alimentary references as narrative strategies or part of the background; Xu takes food as the central site of cultural and political struggles waged in the seemingly private domain of desire in the lives of Asian Americans. For students of literature, this tantalizing work offers an illuminating lesson on how to read the multivalent meanings of food and eating in literary texts.